Penggunaan Fraud Hexagon Theory Dalam Mendeteksi Kecurangan Laporan Keuangan - Widya Syafitri; Rahmaita Rahmaita (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2025)
This study aims to examine the effect of six elements in the Fraud Hexagon Theory pressure, opportunity, rationalization, arrogance, capability, and collusion on financial statement fraud in banking companies listed on the Indonesia Stock Exchange (IDX) during 2021–2024. Financial statement fraud is measured using the Beneish M-Score Model, which applies eight financial ratios to detect potential manipulation. This research employs a quantitative approach with an ex post facto method and a causal design. The sample consists of 43 banking companies selected through purposive sampling, resulting in 172 observations. Data were obtained from annual reports and financial statements published on the official IDX website. Multiple linear regression analysis was conducted, preceded by classical assumption tests to ensure model validity. The findings indicate that pressure, opportunity, and arrogance have a significant positive effect on M-Score, while rationalization, capability, and collusion have a positive but insignificant effect. These results emphasize that pressure, opportunity, and arrogance in leadership play a crucial role in increasing the risk of financial statement fraud in the banking sector. The practical implication is the need to strengthen corporate governance, enhance the effectiveness of internal controls, and enforce managerial ethics to reduce the potential for fraud. For regulators such as the Financial Services Authority (OJK), these findings can serve as input for designing more comprehensive fraud prevention policies.